2022
DOI: 10.1002/jsfa.11823
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial and bioactive properties of lactobionic acid

Abstract: Lactobionic acid (LBA) is a bioactive molecule that has generated keen interest in different industries. However, its future application in the food area is one of the most promising. Chemically, it is a polyhydroxy acid formed by the union of two molecules (galactose and gluconic acid) linked by an ether-bond, showing many interesting and unusual properties due to its structure and composition, although it is traditionally known in the food industry for its chelating, moisturizing, gelling, and antioxidant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…In this study, we identified numerous distinct metabolites and metabolic pathways distinguishing the L. reuteri + LPS group from the control group. For example, L. reuteri + LPS group had a higher concentration of lactobionic acid, which has antimicrobial and bioactive properties such as oxidation resistance and was widely used in the food industry 43,44 . Based on the different metabolites between the two groups, the changed pathways were also analyzed; during these pathways, there were several amino acid metabolism pathways, such as tyrosine metabolism; alanine, aspartate, and glutamate metabolism; phenylalanine metabolism; valine, leucine, and isoleucine biosynthesis, tryptophan metabolism; and arginine and proline metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified numerous distinct metabolites and metabolic pathways distinguishing the L. reuteri + LPS group from the control group. For example, L. reuteri + LPS group had a higher concentration of lactobionic acid, which has antimicrobial and bioactive properties such as oxidation resistance and was widely used in the food industry 43,44 . Based on the different metabolites between the two groups, the changed pathways were also analyzed; during these pathways, there were several amino acid metabolism pathways, such as tyrosine metabolism; alanine, aspartate, and glutamate metabolism; phenylalanine metabolism; valine, leucine, and isoleucine biosynthesis, tryptophan metabolism; and arginine and proline metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, L. reuteri + LPS group had a higher concentration of lactobionic acid, which has antimicrobial and bioactive properties such as oxidation resistance and was widely used in the food industry. 43,44 Based on the different metabolites between the two groups, the changed pathways were also analyzed; during these pathways, there were several amino acid metabolism pathways, such as tyrosine metabolism; alanine, aspartate, and glutamate metabolism; phenylalanine metabolism; valine, leucine, and isoleucine biosynthesis, tryptophan metabolism; and arginine and proline metabolism. The different amino acid metabolism may hint us the changed protein metabolism, which can directly influence the host pathophysiological activity.…”
Section: Discussionmentioning
confidence: 99%
“…These include mineral (e.g., calcium) fortification in beverages, flavor enhancement of fruit preparations, water retention in meat‐based products, and antistaling effects in bread (Cardoso et al., 2019). In addition, LBA has also been shown to have some prebiotic characteristics (Goderska, 2019) and can be used as an antimicrobial in food (Sáez‐Orviz et al., 2022). However, the toxicology of LBA still has not been fully investigated and therefore it has not yet been regulated for use in food in the EU (Cardoso et al., 2019).…”
Section: Indirect Applications (Lactose Derivative and Ingredients)mentioning
confidence: 99%
“…Lactobionic acid (LBA) is composed of gluconic acid linked by an ether bond to a galactose that, according to its structure and composition, has properties of great interest [1]. Tis LBA is a polyhydroxy acid with various proven applications in food, medical, pharmaceutical [2], cosmetic [3], and chemical [4] industries.…”
Section: Introductionmentioning
confidence: 99%